Rescaffolding Carbon Nanotubes in Thermoset Polymers by Heat Treatments - Jen-Kuang Fang; Jen-Chun Chen; Pai-Sheng Shih; Hsuan-Yu Liu; Shu-Huai Hsu; Joey Yeh; Kai-Xiang Hu; Ping-Chun Chen; Hsin-Jung Tsai; Wen-Kuang Hsu (Advances in Polymer Technology)
Due to cross-linked structures, thermoset polymers cannot provide sufficient free volume for nanofillers to maneuver. Related composites are therefore governed by phase separation where filler-deficit regions become mechanical weakness. This work discovers that carbon nanotubes can be redispersed in thermoset polymer through heat treatments, thus, enhancing strength, thermal, and electrical conductivity of composites. Experiments carried out on a different thermoset matrix gives a similar trend where heating induced tube displacement is also verified by molecular dynamic simulations and piezo-resistivity tests.